Ulnar Collateral Ligament Repair With Internal Brace Using Linked Knotless Suture Anchors - Chase Walton, M.S.; Robert J. Reis, B.S.; Megan E. Welsh, B.S.; Richard J. Friedman, M.D., F.R.C.S.C.; Josef K. Eichinger, M.D. (Arthroscopy Techniques, 2024)
This article presents an adaptation of the internal brace ulnar collateral ligament (UCL) repair technique using knotless suture anchors, which shows promise for improved postsurgical functionality and a shortened recovery period in patients with UCL injuries. Traditional methods of UCL reconstruction often require a lengthy 12- to 18-month recovery period, presenting a significant challenge for athletes keen to return to their sport. The modified technique uses smaller sutures and drill holes, thereby eliminating the need for larger anchors and simplifying the surgical process. Furthermore, we provide a comprehensive exploration of the rehabilitation protocol involved after surgery, which includes various phases of physical therapy and use of the “thrower’s ten” program to improve shoulder and elbow stability, strength, and mobility. This technique paves the way for a promising alternative to traditional UCL reconstruction or repair methods, with the potential to significantly enhance clinical outcomes, improve recovery times, and positively impact athletes’ lives.